Risk Factors for 30-Day Readmissions and Reoperations After 3-Column Osteotomy for Spinal Deformity. Issue 5 (August 2018) - De la Garza Ramos, Rafael; Nakhla, Jonathan; Echt, Murray; Gelfand, Yaroslav; Scoco, Aleka N.; Kinon, Merrit D.; Yassari, Reza
Study Design: Retrospective study of a prospectively collected database. Objective: To investigate the rate and risk factors for 30-day readmissions and reoperations after 3-column osteotomy (3CO). Methods: The American College of Surgeons National Surgical Quality Improvement Program database (2012-2014) was reviewed. Inclusion criteria were adult patients who underwent 3CO. The rate of 30-day readmission/reoperation was examined, and the association between patient/operative characteristics and outcome was investigated via multivariate analysis. Results: There were 299 patients who underwent a 3CO for spinal deformity. The rate of 30-day readmission and reoperation was 11.0% and 8.4%, respectively; 7.7% of readmissions were related to the primary procedure and 3.3% were unrelated. The most common unique cause for readmission was wound infection in 27.2% of cases. Among reoperations, the most common unique indications were wound infection (20.0%) and implant-related complications (20.0%). On multivariate analysis, obesity (odds ratio [OR] = 2.96; 95% CI = 1.06-8.25; P = .038), chronic obstructive pulmonary disease (OR = 20.8; 95% CI = 3.49-123.5; P = .001), and fusion of 13 or more spinal levels were independent predictors of readmission (OR = 4.86; 95% CI = 1.21-19.5; P = .025). On the other hand, independent predictors of reoperation included chronic obstructive pulmonary disease (OR = 6.33; 95% CI = 1.16-34.5; P = .033) and chronic steroid use (OR = 6.69; 95% CI = 1.61-27.7; P = .009). Conclusion: Wound complications and short-term implant-related complications are important causes of readmission and/or reoperation after 3CO. Preoperative factors such as obesity, chronic lung disease, chronic steroid use, and long-segment fusion procedures may significantly increase the risk of 30-day morbidity following high-grade osteotomies.